Enabling the City Interdisciplinary and Transdisciplinary Encounters in Research and Practice - Fokdal, Josefine; Bina, Olivia; Chiles, Prue; Ojamäe, Liis; Paadam, Katrin (Taylor & Francis, 2021)
Enabling the City is a collaborative book that focuses on how interdisciplinary and transdisciplinary processes of knowledge production may contribute to urban transformation at a local level in the 21st century, striking a balance between enthusiastic support for such transformational potential and a cautious note regarding the persistent challenges to the ethos as well as the practice of inter and transdisciplinarity. The rich stories reflect different research and local practice cultures, exploring issues such as ageing, community, health and dementia, public space, energy, mobility cultures, heritage, housing, re-use, and renewal, as well as more universal questions about urban sustainability and climate change, and perhaps most importantly, education. Against this backdrop, aspirations for the 21st century are related to the international, national, and local agendas expressed in the Sustainable Development Goals (SDGs) and in the New Urban Agenda (NUA), raising fundamental questions of how to enable development. We highlight aspects of transformative learning and ways of knowing, critical to any collaborative and participatory process.